Pengujian Blackbox Menggunakan Teknik Equivalence Partitions pada Aplikasi Petgram Mobile - Bagus Bayu Sasongko; Fajar Malik; Febry Ardiansyah; Ajeng Fitria Rahmawati; Faisal Dharma Adhinata; Diovianto Putra Rakhmadani (Journal ICTEE, 2021)
Software testing aims to evaluate whether an application is functioning correctly or some errors must be fixed so that the quality of the application is said to be good. Some of the testing methods include Blackbox testing and Whitebox testing, which are often used by testers to evaluate the application according to stakeholder needs or not. This article will examine the Blackbox testing method for evaluating the Petgram mobile application. Evaluations are carried out on the Petgram mobile application on the functional register, login, and make posts. One of the Blackbox method techniques is Equivalence Partitions, a test based on input on each form in the Petgram mobile application, where there are expected results and actual results and successful or failed conclusions. The study results show that there are still some functional failures, especially in the functional register and making posts. The hope is that with the results of this test, the developer can improve it so that the Petgram mobile application becomes of good quality.